2019
DOI: 10.1111/jfb.13915
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian fluid in the three‐spined stickleback Gasterosteus aculeatus: effects of egg overripening and sex steroid treatment

Abstract: The ovarian fluid properties of the three‐spined stickleback Gasterosteus aculeatus were studied in overripe and non‐overripe ovulated female sticklebacks and in females that were implanted with Silastic capsules containing testosterone (T), oestradiol (E2), 17,20β‐dihydroxypregn‐4‐en‐3‐one (17,20β‐P) or progesterone (P4) into the abdominal cavity. Overripe females had less ovarian fluid than non‐overripe females, but with higher dry mass, higher protein concentration and lower viscosity. T and 17,20β‐P increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Moreover, the microvilli-covered cells of the epithelium ovarian cavity have a secretory function to buffer the in vivo environment for oocytes, especially against external constituents via the bloodstream [25]. Accumulation of the OF and its secretory processes were also shown to be modulated by sex steroids, directly and/or indirectly [22,23,26]. In both post-spawning and overripe stickleback, Gasterosteus aculeatus Lam et al [27] showed that sex steroids stimulated OF secretion from ovarian epithelium, where ovaries of progesterone (P4)-treated fish contained a considerable amount of OF in the ovarian cavity than estradiol-17β (E 2 )-treated and control fish.…”
Section: How and Where Ovarian Fluid Is Producedmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the microvilli-covered cells of the epithelium ovarian cavity have a secretory function to buffer the in vivo environment for oocytes, especially against external constituents via the bloodstream [25]. Accumulation of the OF and its secretory processes were also shown to be modulated by sex steroids, directly and/or indirectly [22,23,26]. In both post-spawning and overripe stickleback, Gasterosteus aculeatus Lam et al [27] showed that sex steroids stimulated OF secretion from ovarian epithelium, where ovaries of progesterone (P4)-treated fish contained a considerable amount of OF in the ovarian cavity than estradiol-17β (E 2 )-treated and control fish.…”
Section: How and Where Ovarian Fluid Is Producedmentioning
confidence: 99%
“…In both post-spawning and overripe stickleback, Gasterosteus aculeatus Lam et al [27] showed that sex steroids stimulated OF secretion from ovarian epithelium, where ovaries of progesterone (P4)-treated fish contained a considerable amount of OF in the ovarian cavity than estradiol-17β (E 2 )-treated and control fish. Moreover, in non-overripe ovulated female sticklebacks, implants of fish with testosterone (T) and 17,20β-dihydroxypregn-4-en-3-one (17,20β-P) increased the quantity of OF secretions [26]. Sex steroid hormone concentrations in fish OF were also measured in mature females, where progesterone showed higher concentrations in OF than blood serum (~1.20 ng/mL in serum vs. ~1.40 ng/mL in OF; [28]), but in goldfish, Carassius auratus progesterone exhibited a similar concentration in both OF and serum at ovulation and the level declined during egg over-ripening [29].…”
Section: How and Where Ovarian Fluid Is Producedmentioning
confidence: 99%
“…1989; Piferrer 2001; Huang et al. 2015; Roufidou and Borg 2019). Typically, an increased GSI is only observed in estrogen‐treated males while being decreased in females (Zha et al.…”
Section: Discussionmentioning
confidence: 99%
“…The effects that E2 treatments have on ovarian development and condition vary depending on the species. Most species, including the Threespine Stickleback Gasterosteus aculeatus, Goldfish, and Common Carp, exhibit reduced ovary size and reduced GSI values when exposed to exogenous estrogen (Komen et al 1989;Piferrer 2001;Huang et al 2015;Roufidou and Borg 2019). Typically, an increased GSI is only observed in estrogen-treated males while being decreased in females (Zha et al 2007;Lei et al 2013).…”
Section: Mean Percentage Of Males 95% CI For Percentage Of Malesmentioning
confidence: 99%